Testing Hadronic Interactions at Ultrahigh Energies with Air Showers Measured by the Pierre Auger Observatory - Pierre Auger collaboration (437 authors); Abreu, Pedro; Andringa, Sofia; Assis, Pedro; Blanco, Alberto; Cazon, Lorenzo; Conceição, Ruben; Diogo, Francisco; Espadanal, Joao; Lopes, Luis; Pimenta, Mário; Santos, Eva; et al. (My University, 2016)
Ultrahigh energy cosmic ray air showers probe particle physics at energies beyond the reach of accelerators. Here we introduce a new method to test hadronic interaction models without relying on the absolute energy calibration, and apply it to events with primary energy 6-16 EeV (E_CM = 110-170 TeV), whose longitudinal development and lateral distribution were simultaneously measured by the Pierre Auger Observatory. The average hadronic shower is 1.33 +- 0.16 (1.61 +- 0.21) times larger than predicted using the leading LHC-tuned models EPOS-LHC (QGSJetII-04), with a corresponding excess of muons.